Isolating Student, School, and Community Effects on School Weapon Carrying - Watkins, Adam Michael (2007)
Much prior research has alluded to the importance of community conditions in shaping levels of violence in around and schools. It is interesting to find, therefore, that few studies have systematically examined the effects of broader contextual characteristics (e.g., economic disadvantage) on levels of student misbehavior in schools. This research filled a part of this void in the school violence literature by using data from the National Longitudinal Study of Adolescent Health to identify whether social conditions in schools¿ attendance areas were statistically related to levels of student weapon carrying across a national sample of 55 high schools. Multilevel models estimated in this research revealed that levels of economic disadvantage, residential mobility, and violent crime in schools¿ attendance areas were unrelated to between-school variation in student weapon carrying. Similar null findings were found when examining levels of gun carrying among male students in the sample. Specifically, social conditions in schools¿ attendance areas were also unrelated to between-school variation in gun carrying among male students. Current findings, therefore, offer no support for the conventional wisdom that community conditions discernibly affect levels of weapon carrying in and around schools (i.e., spillover hypothesis). Consequently, current findings are unable to challenge the implementation of many school-based violence prevention programs that do not attempt to manipulate or change social conditions external to schools (i.e., individual-change interventions). Finally, the limitations of this research are thoroughly discussed in order to address how future research can further advance the systematic study of the effects of community conditions on violence in and around schools